Exploring the embodiment of a secondary mathematics teacher - Rawane, Mosima Gladys (University of Limpopo, 2016)
Sarton (1936) stated that mathematics has grown so large for a single mind to grasp. Mack (1961) attributes that phenomenon by claiming that mathematics differs from science in that it keeps on adding new concepts to existing ones, whereas in science there is reduction of concepts. This continuing growth makes it impossible for an individual to study mathematics as a whole (Krantz, 2010). Van Bendegem (2009, p. 137) calls the mathematics world a “mad world”. Recently, Ellerton (2014) compared mathematics to a growing tree. A number of challenges arise out of the observations made above. Is the mathematics that is taught in secondary schools an appropriate reflection of the mathematics that is out there today? Is an individual an appropriate embodiment of a secondary mathematics teacher? In the mist of these and many other questions, this study locates itself in the second question and investigated the notion of an embodiment of a secondary mathematics teacher. The main research question that was pursued was ‘How adequate is an individual as an embodiment of a secondary mathematics teacher?’ This question should be understood and interrogated in the context of Festinger’s (1962) dissonance cognitive theory that also serves as the theoretical framework for the study. The expectations of a secondary mathematics teacher do not fit in with an individual’s capacity to embody those. Grounded theory (Glaser, Strauss & Beer, 1967) was used to generate and develop what Elliot and Higgins (2012) called a substantive theory. This was a desktop grounded theory study and data was collected from existing literature of published journals and books. Since the use of documents is recommended as one of the qualitative data collection methods in grounded theory (Strauss & Corbin, 1990), the documents served as primary data where only a few that were relevant to the issues discussed were selected (Breckenridge & Jones, 2009). Content and thematic analyses procedures were used. Content analysis assisted to organise data according to various eras, tracing the growth in mathematics education and mathematics content, comparing them to a mathematics teacher of different eras, which assisted in bringing the answer to the research question posed (Bowen, 2009). Thematic analysis was used to identify commonalities and differences with regard to the notion of a teacher in various eras (Fereday & Muir-Cochrane, 2006). The findings revealed that the notion of a secondary mathematics teacher of the current era is completely not a suitable embodiment of a secondary mathematics teacher. The current notion of an embodiment of a secondary mathematics teacher is seriously challenged by this ever growing subject. Secondary mathematics is so large for an individual to acclimatise with (Sarton, 1936), and there seems to be a need for more than an individual to ensure that mathematics is well taught and learned by learners. It is recommended that other studies should be undertaken to determine as to how many individuals can constitute a composite suitable to embody the requirements of an ideal secondary mathematics teacher.
Thesis (M. Ed. (Mathematics Education)) --University of Limpopo, 2017
Keywords: Mathematics teachers; Secondary mathematics teachers; Mathematical readiness; Mathematics -- Study and teaching (Secondary) -- South Africa; Mathematics teachers -- Training of